Rethinking Mental Healthcare Disparities: The Role of Social Drivers Beyond Poverty - Alexandra Balshi; John P. Dempsey; Victoria P. Schulte; John Torous (Mental Illness)
Conclusions and Relevance: We demonstrate that after controlling for numerous previously established SDoMH, income did not influence mental healthcare access. Our findings suggest a reconsideration of traditional frameworks that uphold poverty as the primary factor contributing to mental illness and the largest barrier to mental healthcare, suggesting that the socioeconomic factors that drive income disparities in the United States may be what truly shape mental healthcare access.